Kill Zone - Sai Krishna Kamepalli; Raghuram G. Rajan; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2020)
We study why high-priced acquisitions of entrants by an incumbent do not necessarily stimulate more innovation and entry in an industry (like that of digital platforms) where customers face switching costs and enjoy network externalities. The prospect of an acquisition by the incumbent platform undermines early adoption by customers, reducing prospective payoffs to new entrants. This creates a "kill zone" in the space of startups, as described by venture capitalists, where new ventures are not worth funding. Evidence from changes in investment in startups by venture capitalists after major acquisitions by Facebook and Google suggests this is more than a mere theoretical possibility.
Keywords: 330; Gründungsfinanzierung; Risikokapital; Innovation; Wettbewerb; Unternehmensnetzwerk; Social Web; Digitalisierung; Theorie